The Effect of Metaldehyde on Anabas Testudinues - Muhamad Nur Ariff Muhamad Hakim (School of Environmental Engineering, University Malaysia Perlis, 2015)
To monitor the behavioral changes of the fish when being exposed to the pesticides at a significant range of pesticides on fish. To observe physiological changes of the fish when exposed to pesticides. To investigates the acute effect of pesticides on fish.